The Influence Awareness, Reform Administration, Attitude, and Accountability Service Public to Obedience Required Tax Vehicle Motorized on Office SAMSAT UPT PPD BP2RDSU Button Park - Tria Maulina Fatima; Alisraja Dison Silalahi (PT Inovasi Pratama Internasional, 2022)
This research aims to know Awareness, Reform Administration, Attitude, and Accountability of Public Services to Compliance Required Tax Vehicle Motorized At the Office Samsat UPT PPD BP2RDSU PAKAM LUCK. The level of taxpayer compliance is still relatively low seen from the data on the percentage of taxpayer compliance, and the number of taxpayer obligations at the Samsat Office of UPT PPD BP2RDSU LUBUK PAKAM. Public Service Awareness, Administrative Reform, Attitude, and Accountability is factor important which could influence obedience Required tax in pay vehicle tax. This research using approach quantitative with type study, Interview, observation, and share questionnaire. Data analysis techniques which used is analysis regression linear multiple. Based on results In this study, the awareness variable (X1) is the result of a sig value of 29.5% > 5% then it is rejected and the t value is 1.053 < t Table 1983 then rejected, administrative reform variable (X2), namely the result of the sig value of 2% < 5% so received and score t Count 2,374 > t Table 1983 so also received, variable Attitude (X3) is the result of the sig value of 0% <5% then it is accepted and the value of t Count 6.433 > t Table 1.983 then it is also accepted, and the Accountability variable Service Public with results score sig as big as 5% < 5% so received and score t Count 2,893 > t The 1983 table is accepted.